Abdul Aziz Ishak: Biografi Politik 1955 hingga 1962 - Mohamad Idris, Saleh (2013)
This is biographical research of Abdul Aziz (Aziz), the Minister of Agriculture in the cabinet of Tunku Abdul Rahman Putra Al-Haj (Tunku). Aziz was an important figure in the struggle for Malay economic development, particularly in the agricultural sector around the 1950's. The objective of this study is to investigate the background, thoughts, actions and political impact throughout Aziz’s involvement in the cabinet from 1955 until 1962. The qualitative method using the content analysis approach was adopted in the research. Both primary and secondary sources were used in the study. The primary sources included materials in archives such as the private collection of Aziz and his family, minutes of meetings, memos, government records, and parliamentary debate. While the secondary sources came from books and newspapers. In addition, interviews were carried out with family members and those associated with Aziz. The study found that Aziz was instrumental in developing the agricultural sector and improving the living standards of the rural population. He achieved success when he implemented several ground breaking ideas which included the introduction of a paddy and fish marketing project, modernization of the agricultural sector, the use of urea fertilizer and twice a year rice planting scheme, the use of improved and better quality seeds and the introduction of larger boats and better quality fishing nets. He also set up cooperatives throughout the country to curb the activities of middlemen. Aziz’s thought and actions were considered revolutionary. They were never implemented before this by any parties, but it was not viewed favourably by the Tunku who was known to be pro-capitalist and western in outlook. He accused Aziz of deliberately seeking support and popularity among the people this resulted in a conflict between the Tunku and Aziz. Aziz who stood firm and uncompromising in his struggle and was eventually sacked from the Cabinet and it ended his political career while trying to protect the progress and development of the agricultural sector and the Malays.